2012
DOI: 10.1192/bjp.bp.111.095125
|View full text |Cite
|
Sign up to set email alerts
|

Migration and autism spectrum disorder: population-based study

Abstract: BackgroundMigration has been implicated as a risk factor for autism, but evidence is limited and inconsistent.AimsTo investigate the relationship between parental migration status and risk of autism spectrum disorder, taking into consideration the importance of region of origin, timing of migration and possible discrepancies in associations between autism subtypes. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
186
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(204 citation statements)
references
References 36 publications
14
186
1
3
Order By: Relevance
“…One is that the occurrence of neurodevelopmental outcomes may have differed in children participating in CATSS with completed A-TAC assessment and those in the general population. Two Swedish studies found that children of immigrant parents had impaired psychological health (Gillberg et al, 1987;Magnusson et al, 2012;Van Leeuwen et al, 2012); however, the occurrence of neurodevelopmental disorders in our study was lower in families with both parents from outside of Scandinavian countries. The data linkage to other registers allowed us to acquire additional data on the CATSS non-responders, which indicated that children enrolled in the study had higher familial socio-economic status.…”
Section: Figurecontrasting
confidence: 84%
“…One is that the occurrence of neurodevelopmental outcomes may have differed in children participating in CATSS with completed A-TAC assessment and those in the general population. Two Swedish studies found that children of immigrant parents had impaired psychological health (Gillberg et al, 1987;Magnusson et al, 2012;Van Leeuwen et al, 2012); however, the occurrence of neurodevelopmental disorders in our study was lower in families with both parents from outside of Scandinavian countries. The data linkage to other registers allowed us to acquire additional data on the CATSS non-responders, which indicated that children enrolled in the study had higher familial socio-economic status.…”
Section: Figurecontrasting
confidence: 84%
“…100 According to a Swedish study, migrant parents from countries with a low ranking on a human development index may be at increased risk of having children with ASD and comorbid ID compared with Swedish-born parents, particularly when migration occurred around time of pregnancy, suggesting a possible link with maternal stress. 249 However, migrant parents from developing countries may have a decreased risk of having children with PDD-NOS or Asperger.…”
Section: Immigrant Statusmentioning
confidence: 99%
“…Maternal immigrant status is another social factor that emerged in eight studies 104,208,243,[247][248][249][250][251] and two systematic reviews 13,100 supporting an association with ASD or ASD subtype. Migrant mothers had a higher prevalence of offspring with ASD in studies from Sweden, the United Kingdom and Australia.…”
Section: Immigrant Statusmentioning
confidence: 99%
“…Although the specific mechanisms behind childhood autism are largely unknown, risk factors include male sex [1], familial history of autism [1,2], advanced age in either parent at childbirth [3][4][5], neuropsychiatric disorders [6], perinatal complications [7], ethnic background and migration [8,9], and low socioeconomic status [7,10,11]. In addition to these individual-level factors, it is possible that certain social features of the neighborhood environment are associated with autism.…”
Section: Introductionmentioning
confidence: 99%